At the Intersection of Sexual Minority and Transgender or Gender Diverse (SM-TGD) Identity and Mental Illness - Livingstone, Bridget (University of Waterloo, 2020)
Sexual minority and transgender or gender diverse (SM-TGD) persons experience disproportionately high rates of mental illness, substance misuse, and suicide, which are often exacerbated by experiences of social exclusion and marginalization. While healthcare institutions are increasingly aiming to provide affirming mental health care to this population, many mental health services and practitioners remain unresponsive to SM-TGD individuals’ unique identities, needs, and experiences. Despite the fact that mental illness and access to adequate care are pressing concerns for this population, the ways that SM-TGD persons understand mental illness and their experiences navigating the healthcare system have not been adequately studied. Based on data from 12 qualitative interviews conducted in southern Ontario, this study explores the ways that SM-TGD individuals make sense of and contextualize their experiences of mental illness. This study also discusses some of the barriers to care often encountered by this population, and points to the ways that informal barriers such as microaggressions are as impactful as structural barriers, such as wait times. In doing so, this study aims to unveil the complex subjectivities that emerge when exploring the intersection of marginalized identities and experiences of mental illness.
Keywords: mental health; LGBTQ; sexual minority; transgender and gender diverse; microaggressions; subjectivity